Few-layered 1T-MoS2-modified ZnCoS solid-solution hollow dodecahedra for enhanced photocatalytic hydrogen evolution. Issue 14 (20th March 2019) - Mao, Qing; Chen, Jianmin; Chen, Huirong; Chen, Zhijie; Chen, Junying; Li, Yingwei
Abstract : Novel few-layered 1T-MoS2 -modified ZnCoS solid-solution hollow dodecahedra were fabricated for enhanced photocatalytic hydrogen evolution. Abstract : Enhancing solar hydrogen production efficiency essentially relies on the modification of low-cost and highly stable photocatalysts with enhanced light-harvesting ability and promoted charge transfer kinetics. Herein, we report a facile synthetic route to modify the performance of a low-cost metal sulfide semiconductor, consisting of bimetallic metal–organic framework (MOF)-templating and simultaneous sulfidation of the photocatalyst and loading of a MoS2 co-catalyst. The mutual sulfur atom shared by all the transition metal sulfides allows the formation of a ZnCoS solid-solution structure and the stabilization of the metallic 1T-MoS2 phase, contributing towards the photocatalytic activity enhancement in several ways: (i) extending the light absorption region from the UV to visible and near-infrared light by the incorporation of another transition metal sulfide species, i.e., CoS; (ii) achieving abundant catalytically active sites, and high electronic conductivity between the close contacted ZnCoS and MoS2 by loading few-layered 1T-MoS2 ; and (iii) further increasing the capability of utilizing a single photon with relatively higher energy in the UV-visible region via the involvement of a metal-free photosensitizer, Eosin Y (EY). As a consequence, the novel few-layered 1T MoS2 -modified hollow Zn0.5 Co0.5 S rhombic dodecahedra exhibited a high photocatalytic H2 production activity of 15.47 mmol h −1 g −1 with an apparent quantum efficiency of 30.3% at 420 nm and stability with 90% H2 evolution retention even after seven consecutive runs for a total of 35 h of irradiation. This novel approach to prepare advanced materials could be further extended to the phase-controllable preparation of MoS2 and the discovery of other transition metal chalcogenides with high activity and stability for use in various applications.